Adsorption of Lead Ion in Water Solutions using Kaolin-Surfactant Modified as Adsorben - Alfian Putra; Novia Lestari; Hesti Meilina (Balai Riset dan Standardisasi Industri Pontianak, 2015)
Kaolin is one of the natural adsorbent materials. The adsorption ability of kaolin is still low and need to be modified with organic compounds such as surfactants. This research aimed to optimize the lead adsorption in a waste water using modified kaolin. This study modified kaolin adsorben with cationic surfactants which have activated on temperature 300oC during 3 hours in a furnace. The comparison of kaolin and surfactant were 1:0, 1:2, 1:3 and 2:1, respectively while adsorption time were 30, 60 and 90 minute. Lead was used as the artificial waste at a concentration of 100 ppm. The waste from municipal reservoir water storage of Lhokseumawe was used as a benchmark and application. The sample was analyzed by using AAS and characterized by FTIR. The modified adsorben kaolin-surfactan 1:2 gained the highest reduction of efficiency 78% while the lead ion of municipal waste decreased from 4.65 ppm into 2.67 ppm.